2010
DOI: 10.2478/v10181-010-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones in the cerebrospinal fluid of the third ventricle of adult female sheep during different periods of reproductive activity

Abstract: Thyroid hormones (THs) are obligatory for transition from breeding season to anestrus in sheep. In this process, THs act during a very limited time of the year and primarily within the brain. In ewes chronically equipped for sampling cerebrospinal fluid (CSF) from the third ventricle, we have characterized the concentrations of total and free thyroxine (T4), triiodothyronine (T3), and total reverse T3 (rT3) in the CSF during breeding season, anestrus and during a critical period required for transition to anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our model allowed us to continuously monitor Q metabolites’ presence in urine, blood plasma and CSF following oral administration of dry onion skin. The necessary surgical procedures were developed on the basis of stability of skull structures allowing precise cannula placement for long‐lasting collection of CSF without any side effects for a couple of months . One might claim that pigs, due to their digestive tract similarities to humans, are a better animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Our model allowed us to continuously monitor Q metabolites’ presence in urine, blood plasma and CSF following oral administration of dry onion skin. The necessary surgical procedures were developed on the basis of stability of skull structures allowing precise cannula placement for long‐lasting collection of CSF without any side effects for a couple of months . One might claim that pigs, due to their digestive tract similarities to humans, are a better animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Although Szczepkowska et al (2012) concluded that VEGFA may be involved in the photoperiodic plasticity of ChP capillaries, she found only slight changes in VEGFA expression between LD and SD photoperiods in estradiol-implanted and ovariectomized sheep ( Skipor et al, 2010 ). Our study demonstrated in the same animal model that acute fasting (72 h) and photoperiod both modulated VEGFA and VEGR2 protein concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Located within the cerebral ventricles, the ChP bridges the blood and CSF. The ChP and CSF are integral in the neuroendocrine regulatory systems that govern seasonal reproduction in animals and particularly in sheep, and ChP operation is strongly guided by photoperiods (Szczepkowska et al, 2020). Notably, protein levels in the ovine ChP related to tight junctions are higher during short days (SD) than LD, leading to differences in the permeability of the BCSFB and thus the ability of molecules to access the CSF from the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram of the experiment is presented in Figure 10. One month before the experiment, ewes were implanted with stainless-steel guide cannulas in the third ventricle of the brain for the long-lasting collection of CSF, as described earlier [39]. On the morning of the experiment, ewes were implanted with the jugular vein catheter and placed in individual cages.…”
Section: Animals and Experimental Designmentioning
confidence: 99%